Rapid weight gain following weight cutting in male professional boxers - Murugappan, K. R.; Reale, R. R.; Baribeau, V.; O`Gara, B. P.; Mueller, A.; Sarge, T. (The Physician and Sportsmedicine, 2022)
Objectives Weight classifications are used in boxing and other combat sports to match opponents of similar size. Professional boxers commonly engage in a potentially harmful practice known as rapid weight loss or `weight cutting` to make weight the day prior to competition before rehydrating and refueling. This investigation describes the prevalence and magnitude of rapid weight gain in boxers following weigh-in as well as differences in practice with respect to weight class and promotion.